A computational design approach for composite structures at the early embodiment design stage - Klein, Daniel; Malezki, Waldemar; Wartzack, Sandro (NAFEMS World Congress 2015, 21. - 24. Juni, San Diego, USA, NAFEMS World Congress, 2015)
The design of composite structures is a big challenge because a lot of different and mutually dependent parameters like the fiber orientation, the stacking sequence or the layer thicknesses have to be defined. Additionally, even small deviations of these parameters from the ideal can significantly reduce the mechanical properties of the composite part which makes the design of composite parts particularly challenging. Therefore, it is essential to use novel simulation tools and computational methods as soon as possible in the design process. However, many existing software tools are based on a sequence of complex optimization algorithms or are highly restricted, and therefore, not suitable for the early embodiment design of composite parts. Within the intended paper a novel simulation based design approach will be presented which offers a high freedom in design and is based on simple engineering considerations. The design approach can be divided into four different steps: Step 1: Modified Multi-Layer CAIO Method Step 2: Cluster-algorithm Step 3: Defining the stacking sequence Step 4: Compute layer thicknesses In the first step of the design approach the so called Modified Multi-Layer CAIO method is used to compute the ideal fiber orientations and stresses for each load case in an iterative process. As input for this method a FE model for each load case with an arbitrary number of layers and fiber orientation is created and each model is solved separately. For each model the mean stress directions are computed and the elemental fiber orientations in the FE models are oriented in direction of the maximum mean stresses. These modified models are solved again and the process is repeated as long as there is a significant change in the mean stresses. Based on the results of the Modified Multi-Layer CAIO, the number of layers for each finite element as well as the needed fiber orientations can be computed. However, since every element can have a different fiber orientation and number of layers, the computed laminate structure is not manufacturable. For this reason, a cluster algorithm is needed (step 2) to find areas with equal fiber orientation and, therefore, areas where patches could be placed. The basic principle of the cluster algorithm is to choose a first layer of an arbitrary starting element and compare the fiber orientations of this layer to all layers in the neighboring elements. If the comparison of the fiber orientations is positive the neighboring layer is added to the first cluster. For this grown cluster again all the neighboring elements are checked and the comparison process repeats until no new layer can be added to the existing cluster. In this case a new starting element is chosen and the procedure starts again to form a new cluster.  In the end, the clusters are highlighted and a possible patch structure is shown which helps product developers to define a first laminate. However, the ideal stacking sequence as well as the thickness of each layer is still unknown at this stage. Therefore, steps three and four have to follow. In step three the stacking sequence is defined with the help of the stresses which were computed in step 1. The fiber orientations of the patches are compared to the mean stresses in each of the arbitrary layers and a value for the overlapping is computed in each position. The stacking sequence with the highest overall overlapping value is chosen. In the last step (step 4), a FE model is created with the computed stacking sequence and the thicknesses are defined with a simple genetic algorithm.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.acompu
Keywords: Composites; Leichtbau; Simulation